Identity Statuses throughout Adolescence and Emerging Adulthood: A Large-Scale Study into Gender, Age, and Contextual Differences. Issue 1 (4th April 2017) - Verschueren, Margaux; Rassart, Jessica; Claes, Laurence; Moons, Philip; Luyckx, Koen
Identity formation constitutes a core developmental task during adolescence and emerging adulthood. However, it remains unclear how identity formation may vary across age, gender, and context (education vs. employment) in these developmental periods. The present study used a recently developed model to examine identity statuses or types in a sample of 7, 906 Flemish individuals (14–30 years old; 64% female). As expected, achievement, foreclosure, moratorium, carefree diffusion, troubled diffusion, and an undifferentiated status emerged through cluster analysis. Women were overrepresented in the moratorium status (characterized by high exploration), whereas men were mainly situated in foreclosure and carefree diffusion statuses (both characterized by low exploration, but individuals in foreclosure having strong identity commitments as well). Individuals in the carefree and troubled diffusion statuses, which represent the least adaptive statuses, were youngest. High school students were overrepresented in the diffusion statuses and college students were mostly present in achievement (representing the most mature status) and moratorium. Finally, employed individuals were overrepresented in foreclosure, whereas unemployed individuals were mainly situated in troubled diffusion. In sum, the present study systematically examined relationships between empirically-identified identity statuses and socio-demographic variables in a large-scale sample, generating important information on age, gender, and contextual differences in identity.